El cultivo de la yuca en Cuba - Rodríguez M., S. (International Center for Tropical Agriculture, 1991)
Different aspects of cassava cultivation in Cuba are described, namely agroclimatic regions, climate, prevailing soils, area and production, production systems, clones, and uses. Although cassava is planted on marginal soils with little availability of irrigation, if any, yields have increased as well as crop mechanization (70 percent of the harvest is semimechanized). Research on cassava is the responsibility of the Instituto Nacional de Investigaciones en Viandas Tropicales; among major activities carried out, a germplasm bank has been created and the production of clones Pinera and Senorita generalized. Over 90 percent of the area planted to cassava is cultivated with improved clones. The seed production program of recommended clones guarantees certified propagation material for commercial plantings. A clonal composition also exists that guarantees market supply of roots throughout the yr. The country currently has the material and technical infrastructure necessary for the international exchange of germplasm. Future research will focus on yield increase through the efficient application of cultural practices and the use of improved clones. (CIAT)